INVESTIGATION OF THE ADSORPTION OF PHOSPHATE IN GROUNDWATER ON MODIFIED LATERITE ORE BY CERIUM - Thi Thuy Hat, Dang; Thi Thanh Thuy, Tran; The Anh, Dang; Quang Trung, Do (Journal of Forestry Science and Technology, 2018)
Removal of phosphate from surface water and wastewater has been studied well, but there are a few studies in relation to undergroundwater. In order to increase adsorption capacity for phosphate, natural laterite was used to modify with cerium tetrachloride. Modification condition and characterization of the adsorbent material was investigated. Maximum phosphate adsorption capacity of the activated laterite was found to be 3.88 mg/g. Phosphate adsorption process is good at acid, reduce at neutral medium and alkaline medium. Effects of co-ions, including iron calcium, manganese, ammonium and phosphate on the adsorption were also studied. Iron has a great influence on phosphate adsorption capacity while calcium, manganese and ammonium do not interfere.